FEATURES OF THE CONSTITUTIONAL STATUS OF A PERSON IN MONARCHIES OF THE ARAB EAST (Law and Safety, 2018)
The author of the article observes that the issues of consolidating Islam as a state religion and the main source of legislation in combination with the fixing at the constitutional level of the “Western” concept of human rights is largely out of the question. Since the traditional norms of the state religion – Islam are seriously influenced by the constitutional rights and freedoms of the monarchy of the Arab East, it is unequivocally possible to affirm the purely “European modernization” in this area. Considering this, one should pay attention to a number of features of the constitutional status of a person in these states.On the basis of the current constitutions of the monarchies of the Arab East and political and legal practice the author has demonstrated the features of consolidation of the rights, freedoms and duties of citizens (subjects). It has been concluded that the peculiarities of the constitutional status of a person in the monarchies of the Arab East are that the existing constitutions have consolidated a wide range of principles, rights, freedoms that often go beyond Shariah, but their interpretation is often limited to Islam. The constitutional status appears formally to be substantially upgraded and democratized, but in fact it is not.At the same time, the author of the article provides examples of the activities of the agencies of constitutional justice, which testify to significant changes in the understanding of the established principles, rights and freedoms. The implementation of the agencies of constitutional control and the practical activities of these agencies indicate about significant changes in the understanding of the established principles, rights and freedoms.It should be noted quite a concise list of duties of citizens in these states. At the same time, the duty to observe public order and respect for public morality more closely concerns the respect for the principles of Islam as the state religion and the basis of legislation. Only in the Basic Nizami of Saudi Arabia contains a categorical provision on the practice of Islam and, in fact, it is not permitted to spread another religion. However, the constitutions of other monarchies of this region guarantee freedom of religion.
Keywords: constitutional principles; legal status of a person; rights and freedoms of citizens; duties of citizens; Islamic concept of human rights; Western concept of human rights